What’s ethnicity got to do with it?: Religious and racial politics in Europe - Tol, Marietta van der (Ethnic and racial studies, 2024)
Drawing on sociology, anthropology, constitutional law, and political philosophy, this issue explores how the concept of ethnicity functions as a salient category for understanding the experiences of minorities in Europe today. It considers ethnicity as a powerful means of self-identification and the assertion of differences between as well as within ethnic groups. This issue engages the tension between group-based stigmatization on the one hand, and the reality of increasingly fragmented forms of identification under the influences of de-institutionalization and individualization. It also hones in on the ethnicization and racialization of nationhood under the influence of right-wing identity politics, and the exploitation of ethnic differences for political and electoral purposes. In its engagement with socio-legal studies, this issue considers a number of strategies for alleviating the pressure on ethnic minorities, for example through the use of private sector duties as well as potential innovations of anti-discrimination infrastructures.
Gesehen am 19.06.2024